Promotion of Meaning in Life and Wellbeing Among University Students During the COVID-19 Pandemic via a Service-Learning Subject - Zhu, Xiaoqin; Chai, Wenyu; Shek, Daniel T. L.; Lin, Li (Frontiers in Public Health, 2022)
Utilizing the principle of “learning by doing,” service-learning (SL) course provides a platform for university students to apply academic knowledge in serving the community, reflecting on the serving experiences, deepening their understanding of the knowledge, and further improving their competence, responsibility, wellbeing, and meaning in life (MIL). This study reported university students' changes in psychological wellbeing (positive youth development attributes), subjective wellbeing (life satisfaction), and MIL after taking a SL subject during the COVID-19 pandemic through a one-group pretest-posttest design. Based on the data collected from 229 students (mean age = 20.86 ± 1.56 years, 48.0% females), repeated-measures multivariate general linear model (GLM) analyses revealed that students showed significant positive changes in wellbeing and MIL. In addition, pretest MIL scores positively predicted posttest scores of the two wellbeing measures but not vice versa. As predicted, improvement in MIL among students was closely associated with the positive changes in both psychological and subjective wellbeing measures. These findings suggest that SL participation during the pandemic may promote students' life meaning and foster their wellbeing. Furthermore, MIL and wellbeing may improve simultaneously, and MIL enhancement may further contribute to improvement in psychological and subjective wellbeing. The findings further prove that SL is an effective pedagogy in higher education settings in promoting youth positive development.